EFFORTS TO IMPROVE BEGINNING READING SKILLS THROUGH SYLLABIC METHOD IN GRADE 1 STUDENTS OF MI YAA BUNAYYA - Azmi, Zainul; Hairani, Debby Riana (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
The objectives of this study were: To improve the ability to read beginning Indonesian language through syllabic method in class I MI Yaa Bunayya. This type of research is a class action research of 2 cycles. Each cycle consists of 4 stages, namely planning, action implementation, observation and reflection. The research subjects were first grade students of MI Yaa Bunayya. Data collection techniques using observation. The existence of early reading skills is indicated by an increase in the attitude of students when participating in learning in each cycle. In cycle I got a total score of 165 with a percentage of 55% including the category of poor beginning reading ability. In cycle II, it got a score of 240 with a percentage of 80% including the category of excellent beginning reading ability so that there was an increase from cycle I to cycle II